Diagnóstico biomecánico de la energía producida por el movimiento del cuerpo humano en el pedaleo elíptico y su transformación en energía eléctrica para el Laboratorio de Energías Renovables de la Universidad Politécnica Salesiana, sede Quito, durante el año 2016. - Obando Herrera, Fabio Eduardo (2016)
In this investigation biomechanical diagnosis of energy produced by the movement of the human body in the elliptical pedaling and its transformation into electricity it is done and thus study the transformation of human energy into useful energy (electric) , containing a detailed analysis of the power generation through pedaling on an elliptical bicycle, the kinetic energy of motion of the lower limbs is obtained by a simulation as a 4 – bar mechanism that complies with the law of Grashof ( crank mechanism - rocker ). By the transmission ratio pinion - chain movement that drives a generator, the electrical energy needed are obtained to design a system suitable charging for mobile devices low voltage , producing a maximum load in the shortest possible time originates , plus a loading system was implemented by a battery bank in order to take this power when exercises are performed. Using software, graphs were obtained, voltage - time; current intensity - time power - time, real time in the circuit, the same as via USB, is stored in a database, which will serve to collate it with the calculated data.